UNITED TO SOLVE GLOBAL PROBLEMS - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
GEORGETOWN, PENANG, July 2016 As scientists we can only create a better world by practicing our science and being united together in a common cause to solve global problems, said the newly elected President of Unitas Malacologica (UM), Dr. Terry Gosliner.